2011
DOI: 10.3350/kjhep.2011.17.1.19
|View full text |Cite
|
Sign up to set email alerts
|

Development and validation of a simple index system to predict nonalcoholic fatty liver disease

Abstract: Background/AimsAbdominal ultrasonography is useful for the detection and diagnosis of nonalcoholic fatty liver disease (NAFLD). The aims of this study were to establish a predictive model for the selection of subjects for abdominal ultrasonography for the diagnosis of NAFLD and to assess validity of the model.MethodsThe subjects included 901 people who visited the health examination center of the Busan Medical Center. We conducted multiple logistic regression analyses of potential risk factors to identify inde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
12
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 20 publications
3
12
0
Order By: Relevance
“…In line with our findings, Kotronen et al also reported no significant improvement in diagnostic accuracy by the inclusion of genetic information [14]. Other algorithms to diagnose FLD incorporate different covariates from the ones considered here [15-18], thereby reflecting again the difficulty to select predictors for a generally useful diagnostic model for FLD.…”
Section: Discussionsupporting
confidence: 86%
“…In line with our findings, Kotronen et al also reported no significant improvement in diagnostic accuracy by the inclusion of genetic information [14]. Other algorithms to diagnose FLD incorporate different covariates from the ones considered here [15-18], thereby reflecting again the difficulty to select predictors for a generally useful diagnostic model for FLD.…”
Section: Discussionsupporting
confidence: 86%
“…In this study, eight indexes, i.e. FLI [5], LAP [7,28] (derived in Europe), FSI [29] (derived in USA), FLD index [25], HSI [6], Korea index (by Park et al [30], no official name), NAFLD index [23] and ZJU index [24,31] (derived in East Asia), were included and validated, using a large population of 13,122 subjects in western China. This study confirmed the significance of FLI as a predictor of NAFLD.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have reported an increased mean age of patients diagnosed with fatty liver compared to normal controls [29,32]. This appeared to correspond however to an increased mean WT [32] or BMI [29] with age.…”
Section: Discussionmentioning
confidence: 89%
“…This appeared to correspond however to an increased mean WT [32] or BMI [29] with age. To account for any correlation between weight and BMI with age, in this study, liver fat content was normalized to total body fat and values were compared between age categories.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation